Optimized In vitro propagation and somatic embryogenesis of camu camu (Myrciaria dubia) cultivar Vitahuayo for enhanced commercial production - Adrianzén, Pedro M.; Pinedo Freyre, Sergio Fernando; Valles, Barbara S.; Marapara, Jorge L.; Cobos, Marianela; Rodríguez, Hicler N.; Castro, Juan C. (Agricultural Research Communication Centre (ARCC Journals), 2025)
Background: Myrciaria dubia “camu-camu” a fruit-bearing shrub native to the Amazon, is known for its high vitamin C content. However, variations in vitamin C biosynthesis and accumulation among different cultivars present challenges for commercial production. This study aimed to establish an efficient in vitro regeneration protocol for the Vitahuayo cultivar through callus induction and somatic embryogenesis.